Pengembangan Metode Kansei Engineering dan Design with Intent (DwI) untuk Meningkatkan Respons Emosi Positif dan Daya Persuasif Tampilan User Interface - Saputra, Leotan; Yogasara, Thedy (Universitas Katolik Parahyangan, 2025)
The rise of digitalization has greatly impacted consumer behavior in Indonesia, leading to a significant increase in e-commerce consumption. As businesses compete for market share through digital channels, research has focused on developing methods to create display designs that evoke positive emotions and are persuasive. This study utilized Kansei Engineering (KE) and Design with Intent (DwI) to develop design patterns of user interface that elicit positive emotional responses and are cognitively beneficial. Kansei word data were collected through interviews and user reviews, resulting in five groups of Kansei Word. DwI was then applied to this data to produce a design pattern that enhances positive emotions. The study concludes that KE and DwI are effective in enhancing users' positive emotional responses and experiences, despite the implementation complexities. The integration of these two methods effectively identifies emotional needs and formulates appropriate design patterns to fulfill those needs. However, further research is needed to explore other factors that influence emotional responses, such as brand image, product price, and user reviews. It is important to note that while product design is important, other aspects of business strategy also require attention.